2018
DOI: 10.1002/hec.3646
|View full text |Cite
|
Sign up to set email alerts
|

Physicians, sick leave certificates, and patients' subsequent employment outcomes

Abstract: I analyze how general practitioners (GPs) indirectly affect their patients' employment outcomes by deciding the length of sick leaves. I use an instrumental variables framework where spell durations are identified through supply‐side certification measures. I find that a day of sick leave certified only because the worker's GP has a high propensity to certify sick leaves decreases the employment probability persistently by 0.45–0.69 percentage points, but increases the risk of becoming unemployed by 0.28–0.44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Generally, using absenteeism has several advantages: it can be consistently measured across occupations and industries and is readily available in administrative data sources. Also, we know from previous literature that sick leaves causally affect employment prospects (Ahammer 2018, Markussen 2012) and earnings (Andersen 2010). We also find descriptive evidence for such a relationship: workers with more sick leaves are more likely to become unemployed and earn lower wages, even after adjusting for age (Figure A.4).…”
Section: Iii6 Do Changes In Absenteeism Actually Measure Changes In M...supporting
confidence: 64%
See 1 more Smart Citation
“…Generally, using absenteeism has several advantages: it can be consistently measured across occupations and industries and is readily available in administrative data sources. Also, we know from previous literature that sick leaves causally affect employment prospects (Ahammer 2018, Markussen 2012) and earnings (Andersen 2010). We also find descriptive evidence for such a relationship: workers with more sick leaves are more likely to become unemployed and earn lower wages, even after adjusting for age (Figure A.4).…”
Section: Iii6 Do Changes In Absenteeism Actually Measure Changes In M...supporting
confidence: 64%
“…We find that the change in outside options has a stronger effect on sick leaves with arguably easy-to-fake diagnoses (common cold and low back pain) and those starting on days with good weather.16 If sick leaves were taken purely for health reasons, 16We define common cold and low back pain as potential easy-to-fake diagnoses because their symptoms are not immediately visible to a doctor and hence difficult to verify. To define easy-to-fake diagnoses we follow previous research that connects such sick leaves to shirking (e.g., Ahammer 2018). In our sample approximately 4 percent of sick leaves are due to a shirking diagnosis.…”
Section: Iii6 Do Changes In Absenteeism Actually Measure Changes In M...mentioning
confidence: 99%
“…Thus, they seek help from the GP as GP acts as a gatekeeper before further referral, which leads to more sick leave. In Denmark, it is usually the GP who prescribes the sick leave 37 . In accordance with this hypothesis, a study reported that there was a low frequency of sick leave in individuals with mTBI admitted to a hospital 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Workers may take sick leaves with full wage compensation for at least 6 weeks, provided they produce a medical certificate. These certificates are almost exclusively issued by GPs (Ahammer 2018). In this paper we focus on Upper Austria, which is one of the nine Austrian federal states and has 1.5 million residents, which is around one-fifth of the Austrian population.…”
Section: Ii1 Social Securitymentioning
confidence: 99%